Assessing isometric hamstring strength and asymmetry in elite male soccer players: The influence of knee angle on performance - Smith, P.; Pallotta, H.; Taylor, M. J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Hamstring strain injuries (HSI) are one of the most prevalent musculoskeletal injuries in footballers Following a rise over the last 20 years HSI now make up 24% of all injuries [1]. HSI typically occur during maximal intensity running, during the late swing and early ground contact phase where the hamstring tendon is elongated and the muscle transitions from eccentric to concentric contraction [2]. Isometric testing is often used to measure hamstring strength and imbalances between legs, and to allow practitioners to identify athletes at risk of injury. As average knee joint angle during sprinting ground contact was 27.7 ± 5.6 degrees [3] the aim of this study was to compare testing at 0 to 30 degree knee angles to determine if 30 degrees is a more appropriate position for assessing strength. METHODS: 42 professional and semi-professional male soccer players performed isometric hamstring strength testing at a 0 (straight leg, ISOProne) and 30 degrees knee angles (ISO30) using the NordBord device (Vald Performance, Brisbane, QLD, Australia. Tests were performed in a randomised, counterbalanced order, 7 days apart,). Following a standardised warm up, 3, 5 second maximal isometric efforts, separated by 30 seconds recovery were performed. Per leg, peak and average force, and peak and average asymmetry was recorded. Statistical analysis was carried out using a paired t-test and a Pearson correlation coefficient (PCC). Statistical significance was set at p.7 strong [4]. RESULTS: Peak force production was 293 ± 56 N left, 311 ± 60N right in ISOProne, while ISO30 was 351 ±73N left, and 368 ±79N right, p